2018
DOI: 10.1039/c7se00543a
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of graphene oxide with naphthalenediimide diamine for high-performance cathode materials of lithium-ion batteries

Abstract: Naphthalenediimide diamine-functionalized graphene oxide exhibited a high specific capacity and good cyclic stability as a cathode material of lithium batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The TEM image Fig. 2(i) exhibits the multilayer structure as well, further confirming the ultrathin flakes structure of NDIDA-GO [64]. It is worth noting that organic electrode materials are easily dissolved in conventional liquid electrolytes.…”
Section: Structural Characterizationsupporting
confidence: 62%
See 1 more Smart Citation
“…The TEM image Fig. 2(i) exhibits the multilayer structure as well, further confirming the ultrathin flakes structure of NDIDA-GO [64]. It is worth noting that organic electrode materials are easily dissolved in conventional liquid electrolytes.…”
Section: Structural Characterizationsupporting
confidence: 62%
“…It can be seen from Fig. 4(a) that the surface area of NDIDA-GO sample is 14.15 m 2 g À1 , the total pore volume is 0.026 cm 3 g À1 and the average pore diameter calculated by BJH method is 24.42 nm, which is caused by the interspaces of the nanosheet shown in the SEM image [64]. As for the composite material C4Q/PPL, whose surface area and pore structure are smaller than that of biomass carbon PPL, demonstrating that organic electrode material C4Q is well immobilized by PPL (Fig.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…GO-NDIDA exhibits a capacity retention of 100% after 50 cycles with the aid of a conjugated linker (aniline). 131 These results suggested that the introduction of a conjugated linker between graphene and redox-active molecules can improve the electrochemical stability. The functionalization of graphene through the amide bond is a better approach for achieving stability in electrochemical reactions.…”
Section: Small Redox-active Molecule-functionalized Graphene For Libsmentioning
confidence: 98%
“…In the curve of PPD-G, there were many small peaks between the 2θ of about 15-30, indicated that GO was exfoliated to some extent and PPD formed small polymeric crystallites on the GO sheets [36]. The intensity ratio (ID/IG) of the D-peak to G-peak of the Raman spectra of graphene is commonly used to characterize the defect density of graphene [37][38][39][40]. In the Raman spectra of GO and PPD-GO (Figure 4), D peak and G peak appeared around 1310 cm −1 and 1580 cm −1 respectively.…”
Section: The Characterization Of Structure Of Ppd-gomentioning
confidence: 99%